2017
DOI: 10.1007/s11892-017-0929-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Mortality Risks in Migrant South Asians with Type 2 Diabetes: Are We Winning the Battle?

Abstract: Purpose of ReviewWe seek to describe the relationship between diabetes mellitus and cardiovascular risk in migrant South Asians compared to native white Europeans, and to determine the temporal change in this relationship over recent years.Recent FindingsRecent evidence suggests that the excess mortality risk associated with diabetes is lower in the migrant South Asian population compared with white Europeans. By contrast, South Asians continue to demonstrate elevated cardiovascular morbidity compared to white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…In accordance with previous studies, this study reported differences in CVD and cancer risk between white European and South Asian participants 11 25 26. In the future, it might be important to consider that when the high CVD risk among South Asians is better managed in these populations, this may impact on cancer risk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with previous studies, this study reported differences in CVD and cancer risk between white European and South Asian participants 11 25 26. In the future, it might be important to consider that when the high CVD risk among South Asians is better managed in these populations, this may impact on cancer risk.…”
Section: Discussionsupporting
confidence: 90%
“…Although results from the study of Tillin et al 11 were published recently, follow-up started between 1988 and 1991. It was speculated therefore that over time mortality risk may have changed due to an improvement in CVD management 26. In addition, in past decades greater attention has been paid to the differences in disease risk between ethnicities within healthcare, for example, in diabetes screening.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] A hopeful development is that the difference in CV morbidity and mortality between South Asians and Europeans declined after 2000, following the introduction of statins as a standard primary prevention therapy for patients with type 2 diabetes. 21 practice-based), most of our data were either in line or comparable with international data. In addition, our use of double-staged data collection reduced the risk of missing data.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, given the nature of our data set, we did not analyse the temporal changes suggested by some, even though temporal shifts, that is a lower CV risk profile in the younger generation, may well exist. 21…”
Section: Discussionmentioning
confidence: 99%
“…This may arise from the higher diabetes incidence rates seen in younger age groups or may reflect the age distribution of the different ethnic groups. South Asian and black people were observed to present with a different cardiometabolic risk profile, with typically higher HbA 1c , lower BMI, and established micro- and macrovascular complications [ 14 , 31 33 ]. As identified previously by Paul et al [ 14 ], and shown in this cohort, white people with type 2 diabetes had a pattern of presenting with higher BMI at any age compared with South Asian and black people, with larger ethnic differences in BMI levels reported at younger ages.…”
Section: Discussionmentioning
confidence: 99%